A Service-oriented Architecture Based on Windows Communication foundation for Health Monitoring and Tracking (International Journal of Engineering and Computer Science, 2014)
WCF (Windows Communication Foundation) developed by Microsoft, is an ideal SOA (Service-Oriented Architecture) implementation platform. WCF is designed using service oriented architecture principles to support distributed computing where services have remote consumers. SOA generally provides a way for consumers of services, such as web-based applications.SOA is applied to build the web-based management system for Lifeline due to its flexibility and reusability. All services are programmed on .NET. The results of test system which is constructed on .NET show that Lifeline is valuable for practice. The services are deployed, discovered and consumed as a collection of endpoints. A WCF client connects to a WCF service via an Endpoint. Web Services are applications that can be published, located, and invoked across the Internet. Web Services are implemented by SOA .Web Services are applications that can be published, located, and invoked across the Internet. WCF services provide better reliability and interoperability